Psychological Distress in Parents of Autistic Children in Baghdad City - mohammed, Qahtan (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: The study aims to: (1) assess psychological distress in parents of autistic children, (2) identify therelationship between psychological distress and parents' socio-demographic characteristics such as (age, maritalstatus, relationship with child, educational level and monthly income) and (3) identify the relationship betweenparent's distress and some of children' socio-demographic characteristics such as (gender, age, birth order andmean number of children).Methodology: A descriptive–analytical study that was carried out from December 12th, 2011 to May 1st, 2012.on a purposive (non- probability) sample of 120 parents (father and mother) who have children with autism andsend their children to the delayed care centers in Baghdad. Data were collected through the use of theconstructed questionnaire and the process of the self-administrative report. The questionnaire was consisted ofthree parts: parents' socio-demographic characteristics, autistic children' socio-demographic, and parenting stressscale. Content validity of the instrument was determined through the use of panel experts and the internalconsistency of the instrument was determined through the pilot study and the computation of Alpha CorrelationCoefficient (r = 0.83). Data were analyzed through the application of descriptive and inferential statisticalapproaches by using Statistical Package for Social Science (SPSS) version 16.0.Results: The findings revealed that most of sample were mothers in normal marital status who fall in the agegroup 26-35 years old graduated from institute or college and living in nuclear families with barely sufficientmonthly income. Most of the children were firstborn male fall in the age group of 3-7 years and most of familieshave 1-3 children/family. Parents of autistic children are experiencing moderate level of parenting distress. Thereis strong negative relationship between parents' ages with family type and there is moderate relationship amongother variables. There is positive relationship between parenting stress, child's gender and birth order and there isno relationship with other variables.Recommendations: The study recommended providing adequate knowledge for parents about how to deal withtheir child through sessions and brochure; focusing on coping strategies for parents with autistic child should betaken in consideration by media to decrease distress and further studies should be conducted as survey to includeall over the country.